Au quantum dots engineered room temperature crystallization and magnetic anisotropy in CoFe2O4 thin films. Issue 2 (19th November 2018) - Shirsath, Sagar E.; Liu, Xiaoxi; Assadi, M. H. N.; Younis, Adnan; Yasukawa, Yukiko; Karan, Sumanta Kumar; Zhang, Ji; Kim, Jeonghun; Wang, Danyang; Morisako, Akimitsu; Yamauchi, Yusuke; Li, Sean
Abstract : For the first time, this work presents a novel room temperature time-effective concept to manipulate the crystallization kinetics and magnetic responses of thin films grown on amorphous substrates. Abstract : For the first time, this work presents a novel room temperature time-effective concept to manipulate the crystallization kinetics and magnetic responses of thin films grown on amorphous substrates. Conventionally, metal-induced crystallization is adopted to minimize the crystallization temperature of the upper-layer thin film. However, due to the limited surface area of the continuous metal under-layer, the degree of crystallization is insufficient and post-annealing is required. To expose a large surface area of the metal under-layer, we propose a simple and novel approach of using an Au nanodots array instead of a continuous metallic under-layer to obtain crystallization of upper-layer thin films. Spinel cobalt ferrite (CFO) thin film as a 'model' was deposited on an Au nano-dots array to realize this methodology. Our findings revealed that the addition of quantum-sized Au nano-dots as a metal under-layer dramatically enhanced the crystallization of the cobalt ferrite upper layer at room temperature. The appearance of major X-ray diffraction peaks with high intensity and well-defined crystallized lattice planes observed via transmission electron microscopy confirmed the crystallization of the CFO thin film deposited at room temperature on 4 nm-sized Au nano-dots. This crystallized CFO thin film exhibits 18-fold higher coercivity ( H c = 4150 Oe) and 4-fold higher saturation magnetization ( M s = 262 emu cm −3 ) compared to CFO deposited without the Au under-layer. The development of this novel concept of room-temperature crystallization without the aid of additives and solvents represents a crucial breakthrough that is highly significant for exploring the green and energy-efficient synthesis of a variety of oxide and metal thin films.